Crystal structure and optical spectroscopic analyses of (E)-3-(1H-indol-2-yl)-1-(4-nitrophenyl)prop-2-en-1-one hemihydrate - Muhamad Fikri Zaini; Ibrahim Abdul Razak; Wan Mohd Khairul; Suhana Arshad (Acta Crystallographica Section E: Crystallographic Communications, 2018)
The asymmetric unit of the title compound, 2C17H12N2O3·H2O comprises two molecules of (E)-3-(1H-indol-2-yl)-1-(4-nitrophenyl)prop-2-en-1-one and a water molecule. The main molecule adopts an s-cis configuration with respect to the C=O and C=C bonds. The dihedral angle between the indole ring system and the nitro-substituted benzene ring is 37.64 (16)°. In the crystal, molecules are linked by O—-H...O and N—H...O hydrogen bonds, forming chains along [010]. In addition, weak C—H...O, C—H...π and π–π interactions further link the structure into a three-dimensional network. The optimized structure was generated theoretically via a density functional theory (DFT) approach at the B3LYP/6–311 G++(d,p) basis level and the HOMO–LUMO behaviour was elucidated to determine the energy gap. The obtained values of 2.70 eV (experimental) and 2.80 eV (DFT) are desirable for optoelectronic applications. The intermolecular interactions were quantified and analysed using Hirshfeld surface analysis.